Assessment of periodontal status in patients undergoing renal dialysis – A hospital-based study - Akula Nikhila Rani; Madupu Padma Reddy; Suhas Kulkarni; Adepu Srilatha; Loka Suraj Reddy (Journal of Indian Society of Periodontology)
Background: The World Health Organization (WHO) recognized chronic kidney disease as the 12th and 17th leading cause of death and disability in the world, respectively. End-stage renal disease (ESRD) patients undergoing dialysis are also often prone to gingival and periodontal tissue inflammation. Aim: The aim of this study was to assess and compare periodontal status among dialysis patients with age- and gender-matched controls in Hyderabad City, India. Materials and Methods: Cases (n = 165) included people who had been diagnosed with ESRD, while controls (n = 165) were subjects accompanying cases who were matched for age and gender. The oral hygiene behavior (OHB) was assessed using the OHB Index developed by Buunk et al. Periodontal status was assessed using the Community Periodontal Index modified and loss of attachment (LOA) based on the modified WHO criteria 2013. Results: Significantly higher means of OHB were seen among cases. Higher means of bleeding, pocket depth (PD), and LOA were seen with increasing age among males, low level of education, and presence of systemic condition among both cases and controls. The mean number of teeth with pocket depth (PD) >4 mm and the mean number of sextants with LOA >3 mm were significantly higher among cases than controls. At the same time, the gingival bleeding was significantly higher among controls. Regression analysis revealed that subjects who underwent dialysis (cases) and the presence of the systemic condition were only the significant predictors for the presence of periodontal disease. Conclusion: The study concludes that patients undergoing hemodialysis are more prone to periodontal diseases, which are again influenced by systemic conditions.